The yeast SEN1 gene is required for the processing of diverse RNA classes. - Ursic, D (1997)
A single base change in the helicase superfamily 1 domain of the yeast Saccharomyces cerevisiae SEN1 gene results in a heat-sensitive mutation that alters the cellular abundance of many RNA species. We compared the relative amounts of RNAs between cells that are wild-type and mutant after temperature-shift. In the mutant several RNAs were found to either decrease or increase in abundance. The affected RNAs include tRNAs, rRNAs and small nuclear and nucleolar RNAs. Many of the affected RNAs have been positively identified and include end-matured precursor tRNAs and the small nuclear and nucleolar RNAs U5 and snR40 and snR45. Several small nucleolar RNAs co-immunoprecipitate with Sen1 but differentially associate with the wild-type and mutant protein. Its inactivation also impairs precursor rRNA maturation, resulting in increased accumulation of 35S and 6S precursor rRNAs and reduced levels of 20S, 23S and 27S rRNA processing intermediates. Thus, Sen1 is required for the biosynthesis of various functionally distinct classes of nuclear RNAs. We propose that Sen1 is an RNA helicase acting on a wide range of RNA classes. Its effects on the targeted RNAs in turn enable ribonuclease activity.